2016
DOI: 10.1111/his.12863
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre validation of Metasin: a molecular assay for the intraoperative assessment of sentinel lymph nodes from breast cancer patients

Abstract: Aims: Treatment strategies for breast cancer continue to evolve. No uniformity exists in the UK for the management of node-positive breast cancer patients. Most centres continue to use conventional histopathology of sampled sentinel lymph nodes (SLNs), which requires delayed axillary clearance in up to 25% of patients. Some use touch imprint cytology or frozen section for intraoperative testing, although both have inherent sensitivity issues. An intraoperative molecular diagnostic approach helps to overcome so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Six patients (2.4%) were singularly positive for MGB compared with 1.63% in a previous study 21. These patients are significant because their metastases would not be detected by the OSNA system which only detects CK19.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Six patients (2.4%) were singularly positive for MGB compared with 1.63% in a previous study 21. These patients are significant because their metastases would not be detected by the OSNA system which only detects CK19.…”
Section: Discussionmentioning
confidence: 60%
“…Metasin is reliable with a failure rate of just 0.8%, comparing favourably with our routine qRT-PCR techniques (4.9%), a further study of Metasin (1.5%)21 and the OSNA system (1.4%) 22. The reproducibility of Metasin for CK19, MGB and PBGD is excellent for a RT-qPCR assay, where variation in Cq values should generally be <1.5 23…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Over the past decade, many researchers are keen to apply molecular assays to improve intra-operative pathologic accuracy of breast SLNs, such as the Metasin assay [ 18 , 19 ] and one-step nucleic acid amplification assay (OSNA) [ 20 , 21 ], but neglect to give full consideration to the existing mature pathologic techniques (TIC and FS), which are widely used in clinical practice. In addition, a study of OSNA in 552 patients showed both OSNA and TIC can serve as qualified intra-operative assessments of SLNs, and suggested that OSNA can be applied as a complement to histopathologic assessment, but cannot replace pathology with serial sectioning [ 22 ].…”
Section: Discussionmentioning
confidence: 99%